The Benefits and Costs of Bank Mergers - Cohen, Kalman J.; Reid, Samuel Richardson (Journal of Financial and Quantitative Analysis, 1966)
The pros and cons of bank mergers and multiple-office banking are in the forefront of bank policy consideration today [8, p. 19] Commercial banks have Joined the industrial and merchandising files., as well as the transportation companies, to sweil a rising tide of merger; The Comptroller of the Currency has reported that nearly 2, 000 banks with resources of over $40 billion, were acquired by other banks between 1950 and 1962, inclusive, [47, p. ll].